2021
DOI: 10.3906/sag-2103-148
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of mammary Paget’s disease: a single-center experience in Turkey

Abstract: Background/aim: Paget's disease (PD) of the breast is a very rare presentation of breast malignancy, accounting for 1-3% of all primary breast tumors. We aimed to evaluate and compare the clinicopathological featuresand clinical outcome of PD accompanied by in situ carcinoma and invasive cancer. Materials and Methods:We used the archive of our pathology laboratory retrospectively for age, gender, history of surgery, histopathological findings, treatment modalities and follow-up information. We used the Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our study, we determined these periods to be earlier at 39.4 and 42 months, respectively. Kar et al [ 25 ] found the OS for patients with MPD to be 58±9.5 months (95% CI: 39.2–76.7). While 43 of our patients (87.8%) were alive, six of them died during follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we determined these periods to be earlier at 39.4 and 42 months, respectively. Kar et al [ 25 ] found the OS for patients with MPD to be 58±9.5 months (95% CI: 39.2–76.7). While 43 of our patients (87.8%) were alive, six of them died during follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Esta enfermedad suele ser infrecuente y comprende aproximadamente del 1 al 3% de los tumores de mama (15).…”
Section: Discussionunclassified